Comparison of clinical outcome parameters, the Patient Benefit Index (PBI-k) and patient satisfaction after ablative fractional laser treatment of peri-orbital rhytides - Karsai, Syrus; Raulin, Christian (Lasers in surgery and medicine, 2010)
Laser treatment of facial rhytides has evolved as a major modality of aesthetic surgery. Published results, while generally encouraging, feature highly diverse evaluation methods, which makes an evidence-based assessment of treatment efficacy and safety all but impossible. To compare the results of different instruments of measurement.